ANALYSIS OF DIAGNOSIS AND TREATMENT OF SEVERE HEMOLYTIC DISEASE OF THE FETUS - O. V. TURICHENKO; E. E. KORCHAGINA; A. A. LAPIN (Кубанский научный медицинский вестник, 2018)
Aim. The aim of the study is to evaluate the effectiveness of the modern methods of prenatal diagnosis and treatment of hemolytic  disease of the fetus based on the analysis of researchers’ own clinical material accumulated during 12 years.Materials and methods. There was performed a prospective analysis of 210 pregnant women with RH-immunization with noninvasive methods of diagnosis and invasive methods of  treatment of HDF. Also there was conducted the analysis of the introduction of the specialized reception and monitoring of the  maximum systolic circulation rate (MSCR) increase in the middle cerebral artery (MCA) in the diagnosis of anemia of the fetus.Results. The specialized reception of pregnant women with RH-immunization organized at the Perinatal Center in 2005 allowed us to carry out timely diagnostics of the anemic syndrome in the fetus and  made it possible to start the prenatal treatment primarily at the moderate severity stage of anemia. Pregnant women with the  edematous form of HDF entered the PC either with an established  diagnosis or it was determined during the first appointment at the PC.Conclusion. As a result, we proved the effectiveness of the intrauterine treatment of severe forms of anemia in the fetus and showed the effectiveness of such tactics of management of pregnant women with RH-immunization.